Karakterisasi asam humat dan asam fulvat pada ultisol dengan pemberian limbah segar organik dan pengalengan nenas - Susila Herlambang; Azwar Maas; Sri Nuryani Hidayah Utami; Jaka Widada (Universitas Pembangunan Nasional Veteran Yogyakarta, 2017)
The purpose of the study to know characterization of humic and fulvic acids after three months decomposition by fresh organic waste and canning pineapples treatment at Ultisol Lampung. The research was designed with a completely randomized factorial design with three factors in the plot pots 165 cm x 165 cm x 55 cm. The first is fresh organic waste (200 ton.ha-1 chopper pineapple crops, 40 ton.ha-1 cattle manure, 40 ton.ha-1 cassava waste, 40 ton.ha-1 waste pump pineapple, 2 ton.ha-1 mill juice pineapple), and the second is depth on the soil (i.e. 0 - 15 cm, 0 - 30 cm and 0 - 45 cm), the each repeated three replication so total treatments are 24 plot pots. The results showed ameliorant treatment fresh organic waste and canning pineapples can increase the levels of C-organic from <1% to >1.5%. On the control (K0) in two months decomposition did not significantly different at 5%, but the decomposition of humic acid for three months showed significant differences in the treatment of K0, K1 and K2. Utilization of combinations of fresh organic waste and canning pineapples treatment at the depths (0 - 15, 0 - 30 and 0 – 45 cm) can increase the humic acid content about >1.5% in three months decomposition waste. The combination treatment of fresh organic waste and canning pineapples on Ultisol for three months decomposition, able to provide sufficient nutrients especially the availability of C-organic, humic acid and fulvic acid for growth pineapples.